Entrepreneurial Barriers for Women in the First-Class Municipalities of Masbate, Philippines - Teresa A. Aguilar (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This research examined the opportunities and challenges faced by women entrepreneurs in the first-class municipalities of Masbate, Philippines, with a particular emphasis on Aroroy and Milagros. The study yielded a comprehensive document detailing the entrepreneurial status of women employed in small to medium-sized enterprises (SMEs) within the selected municipalities. A mixed-method approach was used in this study which revealed significant economic, socio-cultural, and structural barriers, including limited financial resources, gender biases, and inadequate institutional support. Despite these challenges, women entrepreneurs demonstrated resilience and optimism, with opportunities identified in microfinance, local government initiatives, and potential skill-building programs. The findings emphasized the importance of targeted interventions such as financial aid, mentorship, and improved outreach to bridge knowledge and access gaps. By addressing these barriers and leveraging identified opportunities, this study provides actionable insights that may guide policymakers, support organizations, and the academic community to foster an inclusive entrepreneurial ecosystem that empowers women in rural areas. Overall, the findings of the study reflect the standing of women within the entrepreneurial areas.